„Challenges for repositories!?“ Conference on the occasion of the tenth anniversary of the launch of Phaidra at the University of Vienna (Vienna, October 24, 2017) - Blumesberger, Susanne (Communications of the Association of Austrian Librarians, 2017)
Ten years of experience with the operation of a repository shows that needs and issues are constantly changing. For example, it is necessary to consider which technologies and requirements of different stakeholder groups currently give rise to new or different thinking on repositories, and how current developments in this area can be conceived and implemented. Recent tasks, such as research data management and user habits, are contributing to a changing image of repositories. At this event, experts from various disciplines discussed how the future of repositories might look like, what considerations and resources are needed and necessary.